Digital Curation Education in Practice: Catching up with Two Former Fellows - Lisa Gregory; Samantha Guss (International Journal of Digital Curation, 2011)
From 2008-2010, as part of the grant: ‘DigCCurr I: Preserving Access to Our Digital Future: Building an International Digital Curation Curriculum’ (DigCCurr I) funded through the Institute of Museum and Library Services, a number of fellows at the School of Information and Library Science (SILS) at the University of North Carolina at Chapel Hill (UNC-CH) were comprehensively trained by library and archive professionals in digital curation theory and practice. This paper examines the curriculum skill areas matrix of the DigCCurr I program from the perspective of two former fellows, now employed in professional positions that utilize digital curation principles. Each fellow offers an analysis of digital curation functions and subfunctions as they relate to her current position, deriving suggestions for future iterations of the DigCCurr program and other graduate programs meant to prepare digital curators. While DigCCurr has been reported by its creators, a group of seasoned digital curation professionals and educators from around the world, this paper provides a fresh perspective from graduates of the program who are applying their newly learned digital curation skills and knowledge in the workforce.